It's Milestone, not Limescale! Milestoned group supervision as an approach to descale postgraduate projects - Catarina Lelis (University of West London, 2020)
Postgraduate students often face the constraints of overlapping non-academic duties, for which the timely completion of their degree can become a challenging commitment. Collective supervision grounded in milestones and shareable deliverables can help in providing them with a sense of progression whilst developing confidence in their own work.